Impact of Face-Recognition-Based Access Control System on College Students’ Sense of School Identity and Belonging During COVID-19 Pandemic - Wang, Qiang; Hou, Lan; Hong, Jon-Chao; Yang, Xiantong; Zhang, Mengmeng (Frontiers in Psychology, 2022)
In the context of coronavirus pandemic (COVID-19), the face-recognition-based access control system (FACS) has been intensively adopted to protect students’ and teachers’ health and safety in school. However, the impact of FACS, as a new technology, on students’ attitude towards accepting FACS has remained unknown from the psychological halo effect. Drawn on “halo effect” theory where psychological effects affect the sense of social identity and belonging, the present study explored college students’ sense of school identity and belonging in using FACS during COVID-19 based on the technology acceptance model. Data collected from 391 college students was analyzed using SEM to verify the relationship among perceived usefulness, perceived ease of use, intention to use, school identity, and school belonging. The results show that perceived usefulness and perceived ease of use can positively predict intention to use, and consequentially can positively predict school identity and school belonging. Our study expands the application of halo effect theory to study FACS acceptance based on TAM, and provides strong evidence to support the effect of school FACS during the pandemic. The findings of this study also suggest that FACS acceptance can enhance students’ sense of school identity and belonging.